AKUNTANSI PENDAPATAN RETRIBUSI PEMAKAIAN KEKAYAAN DAERAH PADA BADAN PENGELOLA PENDAPATAN DAERAH PROVINSI JAWA TENGAH - Lenny Nur Fajriyah; Adilistiono - (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2019)
This research aims to determine the accounting process starting from transactions by supporting documents to present them into financial statements. As well as to determine the suitability of processing supporting documents used by the Central Java Province Revenue Management Agency and the accounting treatment of revenue from the use of regional wealth. The method used is the description and exposition method. The description method is used to explain the general description of the Central Java Province Regional Revenue Management Agency, the vision and mission, organizational structure, and duties and exposition method are used to explain the application of accrual basis on the recognition, measurement, presentation and disclosure of Regional Property Usage levies on Central Java Provincial Revenue Management Agency. The results of this final project writing are showing the supporting documents of the Central Java Province Regional Revenue Management Agency has been processed correctly, besides knowing the recognition, measurement and presentation of revenue revenues from the regional wealth management levies in Central Java Province